Development of Sirah Cai Cipelang Tourist Destination on A Regional Based on Village Own Enterprise (BUMDES) Empowerment - Tarlani Tarlani (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
The development of village tourist destinations can accelerate the transformation of the rural economy from 'low value added' status to 'high value added' which impacts expanding employment opportunities, increasing income, and family economic resilience. Cipamekar Village, Sumedang Regency has great potential to become a regional tourist destination, considering the existence of spring and agro-tourism tourist destinations that are easily accessible to the people of West Java when Cisumdawu Toll Road is already operating. Therefore, it is necessary to have a process of empowering BUMDes Tirta Mekar so that the development of sirah cai cipelang tourist destinations uses scientific and innovative approaches. The methodology is carried out by looking directly at BUMDes-BUMDes that have successfully managed their tourist areas to be used as a reference in the development of BUMDes in managing sirah cai cipelang tourism.